2020
DOI: 10.3389/fendo.2020.543845
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Thyroid-Stimulating Hormone Increases the Percentages of Natural Killer T Cells and B Lymphocytes in Human Peripheral Blood In Vivo

Abstract: Multiple cellular and humoral components of the immune system play a significant role in the physiology and pathophysiology of various organs including the thyroid. On the other hand, both thyroid hormones and thyroid-stimulating hormone (TSH) have been shown to exert immunoregulatory activities, which are difficult to assess independently in vivo. In our study we employed a unique clinical model for the assessment of TSH biological function in humans. The structure of peripheral blood mononuclear cell populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Although still a matter of debate, TSH itself has been proposed as a potential regulator of the immune system as different immune cells were shown to express TSHR (for review see ( 107 )). In agreement with this, recombinant human TSH was shown to promote lymphocyte proliferation and activation, including NK, T and B cells in thyroidectomised patients in vivo ( 108 ). Moreover, TSH was suggested to promote thymic T cell development in humans and mice, based on the interaction with thymic T cell expressed TSHR ( 109 ).…”
Section: Tsh Within the Immune Systemmentioning
confidence: 67%
“…Although still a matter of debate, TSH itself has been proposed as a potential regulator of the immune system as different immune cells were shown to express TSHR (for review see ( 107 )). In agreement with this, recombinant human TSH was shown to promote lymphocyte proliferation and activation, including NK, T and B cells in thyroidectomised patients in vivo ( 108 ). Moreover, TSH was suggested to promote thymic T cell development in humans and mice, based on the interaction with thymic T cell expressed TSHR ( 109 ).…”
Section: Tsh Within the Immune Systemmentioning
confidence: 67%
“…A study of athyreotic patients due to total thyroidectomy for differentiated thyroid cancer showed that administration of recombinant human TSH led to a significant rise in the percentage of natural killer T cells and B lymphocytes in their peripheral blood. This showed a potential direct impact of TSH on immune cells, independent of thyroid hormone action ( 28 ). Indeed, in our subgroup analysis, TSH still positively correlated with lymphocyte counts among patients with low fT3, further highlighting the independent association between TSH and lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…This receptor has been found to be expressed on monocytes, dendritic cells, natural killer cells, T and B cells ( 32 ). Stimulation with recombinant human TSH has been shown to promote proliferation of natural killer cells, T and B cells ( 35 ). In dendritic cells, TSH stimulation was shown to lead to the production of pro-inflammatory cytokines and increased phagocytic activity ( 36 ).…”
Section: Tsh Receptor Expressionmentioning
confidence: 99%
“…• Thymic hyperplasia in Graves's Disease • Immune dysregulation in cancer (23,(33)(34)(35)(36) Red blood cells (protein)…”
Section: Author Contributionsmentioning
confidence: 99%